2018
DOI: 10.1136/bmjopen-2018-023102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinicopathological characteristics of mismatch repair-deficient colorectal carcinoma in early onset cases as compared with late-onset cases: a retrospective cross-sectional study in Northeastern Iran

Abstract: ObjectivesLynch syndrome (LS), a genetically inherited autosomal disorder, increases the incidence of colorectal carcinoma (CRC). We aimed to perform a universal strategy to assess the prevalence and clinicopathological characteristics of early onset CRCs at high risk of LS versus late-onset ones in the Iranian population.SettingA local population-based study from Northeastern Iran.Participants321 consecutive CRCs and pathology specimen screened between 2013 and 2016.Primary and secondary outcome measuresRetro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 57 publications
0
25
0
Order By: Relevance
“…Using MSI as the initial screening test, a study from Saudi Arabia reported 11.6% MSI cases [27]. In the Iranian population, 10.57% of the early-onset CRCs were dMMRP [28]. A low frequency (8.4%) of dMMRP was reported in a study from Japan [29], which was the first to evaluate the prevalence of dMMRP in CRC in the young Japanese population, suggesting that this low rate might be related to yet-to-be identified genetic or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Using MSI as the initial screening test, a study from Saudi Arabia reported 11.6% MSI cases [27]. In the Iranian population, 10.57% of the early-onset CRCs were dMMRP [28]. A low frequency (8.4%) of dMMRP was reported in a study from Japan [29], which was the first to evaluate the prevalence of dMMRP in CRC in the young Japanese population, suggesting that this low rate might be related to yet-to-be identified genetic or environmental factors.…”
Section: Discussionmentioning
confidence: 99%
“…Hereditary cancer syndromes, a type of inherited disorder in which there is a higher-than-normal risk of certain types of cancer, are caused by mutations in certain genes passed from parents to children (62)(63)(64)(65)(66). Indeed, certain patterns of cancer may be seen within families, e.g., hereditary breast (65) and lynch syndrome (63).…”
Section: Resultsmentioning
confidence: 99%
“…Hereditary cancer syndromes, a type of inherited disorder in which there is a higher-than-normal risk of certain types of cancer, are caused by mutations in certain genes passed from parents to children (64)(65)(66)(67)(68).…”
Section: Discussionmentioning
confidence: 99%